Penguatan Resilensi Perempuan Melalui Modal Sosial di Era Adaptasi Kebiasaan Baru Pandemi Covid-19 (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: The increasing issue of gender responsiveness to women's burdens as a result of COVID-19 has become the background for the implementation of women-based community empowerment under the name